Effectiveness and Nephrotoxicity of Intravenous Polymyxin B in Chinese Patients With MDR and XDR Nosocomial Pneumonia - Zeng, Huihui; Zeng, Zihang; Kong, Xianglong; Zhang, Hongliang; Chen, Ping; Luo, Hong; Chen, Yan (Frontiers in Pharmacology, 2021)
Background: Nosocomial pneumonia is a major health and economic burden globally. Multidrug-resistant (MDR) or extensively drug-resistant (XDR) Gram-negative bacteria are the most common causative pathogens in critically-ill patients. Polymyxin B is a salvage therapy for MDR Gram-negative pathogens; however, the current literature on its effectiveness and nephrotoxicity is limited, including in Chinese patients. Methods: We retrospectively analyzed 107 patients with nosocomial pneumonia caused by MDR or XDR Gram-negative bacteria treated with intravenous polymyxin B (2–3 mg/kg/day). Renal function was evaluated on the day before commencement of polymyxin B therapy and on the third and 7 days of treatment. Univariate and multivariate analyses were conducted to determine risk factors for the effectiveness and nephrotoxicity of polymyxin B. Sixty-seven (62.6%) and sixty-five (60.7%) patients had favorable clinical and microbiological responses, respectively. Acute physiology and chronic health evaluation II (APACHE II) scores, cardio-pulmonary resuscitation (CPR) history, numbers of pathogens per patient and a favorable microbiological response were independently associated with favorable clinical outcomes of polymyxin B treatment in Chinese patients with MDR or XDR nosocomial pneumonia. Initial renal dysfunction was not associated with late nephrotoxicity (on day 7), although early nephrotoxicity (on day 3) was independently associated with late nephrotoxicity (OR = 39.43, 95% CI 7.64–203.62, p = 0.00). Conclusion: Our findings support polymyxin B treatment for MDR and XDR pneumonia, with the severity of disease and polymicrobial infection being risk factors for a poor clinical outcome. Nephrotoxicity following 3 days of polymyxin B treatment was found to be a reliable risk factor for later nephrotoxicity.